Parents' experiences of VOICE: A novel support programme in the NICU. Issue 3 (29th October 2020) - van den Hoogen, Agnes; Eijsermans, Rian; Ockhuijsen, Henriette D. L.; Jenken, Floor; Oude Maatman, Sabine M.; Jongmans, Marian J.; Verhage, Lianne; van der Net, Janjaap; Latour, Jos M.
Abstract: Background: Admission of an infant to a neonatal intensive care unit (NICU) is often a stressful experience for parents and can be associated with feelings of inadequacy to fulfil the desirable parental role. The values, opportunities, integration, control, and evaluation (VOICE) programme was developed to engage parents in care, to decrease stress, and to increase empowerment. Aim: To explore the experiences of parents regarding involvement in the VOICE programme during admission of their infant to the NICU. Design: The VOICE programme includes at least five personal structured meetings between parents, nurses, and other health care professionals throughout the pathway from birth, NICU, and follow up. A qualitative design was adopted using semi‐structured interviews. Interviews with 13 parents of 11 infants born at <27 weeks' gestational age were conducted: nine mothers and two couples of father and mother. Thematic analysis was deployed. Results: The findings have been described in one overarching theme: "parental empowerment." Parents felt strengthened and were empowered in the development of their role as primary caretaker by the VOICE programme. The parental empowerment theme emerged from four related interpretive themes that were derived: (a) involvement in care, (b) personalized information and communication, (c) transition to a parental role, and (d) emotional support. Conclusion: The VOICE programme can be a structured approach used to implement family support in a NICU to empower parents to become a partner in the care of their infant and feel confident. Relevance to clinical practice: This study encourages health care professionals to provide parental support through a structured intervention programme, which contributes to the empowerment of parents in the NICU and encouraged them to participate in care and decision‐making.